The Scientific Impact Derived From the Disciplinary Profiles - Allik, Jüri; Lauk, Kalmer; Realo, Anu (Frontiers in Research Metrics and Analytics, 2020)
The disciplinary profiles of the mean citation rates across 22 research areas were analyzed for 107 countries/territories that published at least 3,000 papers that exceeded the entrance thresholds for the Essential Science Indicators (ESI; Clarivate Analytics) during the period from January 1, 2009 to December 31, 2019. The matrix of pairwise differences between any two profiles was analyzed with a non-metric Multidimensional Scaling (MDS) algorithm, which recovered a two-dimensional geometric space describing these differences. These two dimensions, Dim1 and Dim2, described 5,671 pairwise differences between countries’ disciplinary profiles with a sufficient accuracy (stress = .098). A significant correlation (r = .81, N = 107, p < .0001) was found between Dim1 and the Indicator of a Nation’s Scientific Impact (INSI), which was computed as a composite of the average and the top citations rates. The scientific impact ranking of countries derived from the pair-wise differences between disciplinary profiles seems to be more accurate and realistic compared with more traditional citation indices.